Efficiency Analysis of Private Higher Education in Indonesia Using DEA Approach - Kamaruddin, Kamaruddin; Sarwani, Husna; Pulungan, Sahmiar; Azhari, A (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
This study measures the relative efficiency level of private higher education in Indonesia between 2017 and 2018. The data was analyzed using the Data Envelopment Analysis (DEA) with the Constant Return to Scale and Variable Return to Scale methods. The input and output variables consisted of the number of lecturers, study programs, and enrolled students graduates, and new entrants, respectively. According to the results, private higher education in Indonesia is not fully efficient. Therefore, future research needs to compare state and private higher education efficiency levels.